Why Bilingual Geography Teaching at Secondary Stage I? - Golay, David (Journal of Geography Education, 2004)
In specialist circles of bilingual subject teaching, experts agree: although there is as yet no indepth, sound didactics, bilingual subject teaching on the most diverse school levels experience a tremendous uptrend; in particular concerning the subject of Geography. "Learning by doing" is still the motto; that is, not only students are taught by linguistic immersion (lat. immergere = immerse) but teachers, too, immerse themselves and embark on this to date little explored adventure. Given the fact that, to this day, already more than a thousand Canadian studies were completed, the empirical research of bilingual teaching has now found its exponents in Middle Europe, too. However, the countless, partly unpublished studies show results that often neglect the theoretical basis to support the respective theses. The following paper attempts, on the example of bilingual lessons in geography, to try and close, at least to some extent, this theoretical gap of the currently emerging bilingual didactics on the basis of own experience in teaching and studies and with the help of reflections on the acquisition of language and the theories of learning.